Examining the experiences of school governing body in handling school funds - Bhekithemba Phumlani Ngema; Simanga Phillip Lukhele; Rudzani Israel Lumadi (International Journal of Educational Management and Development Studies)
This study aimed at examining the experiences of finance committee, the sub-committee of the School Governing Body (SGB) in managing finances in selected schools in the uMkhanyakude District, KwaZulu-Natal Province, South Africa. Thus, the study’s primary aim was achieved through the identification of hindrances that prevented the finance committee from effectively managing school funds. Moreover, the exploration of strategies to overcome challenges the finance committees faced were also part of the study’s objectives. The study sampled four secondary schools in the uMkhanyakude District as research sites. That is, four principals, four treasurers, and four finance officers were purposefully selected to participate in the study. Data were collected through qualitative semi-structured face-to-face interviews and document analysis and were analysed and interpreted using themes and sub-themes. The study revealed that some finance committee members, especially principals and finance officers, were aware of their roles and responsibilities in the committee; the parents lacked basic literacy skills in managing school funds; the state deposits school finances into the schools’ coffers accounts late, and the state deposits insufficient funds into the schools’ accounts. Therefore, the findings implied that the Department of Education should conduct ongoing training sessions for the finance committee members, especially the parents. Subsequently, professionals with an Accounting degree should perhaps facilitate the training. Moreover, the KwaZulu-Natal Department of Education should deposit adequate funds timeously and in accordance with the inflation rate of the country to avoid recurring debts.